Tax competition and tax structure in open federal economies: evidence from OECD countries with implications for the European Union - Timothy J. Goodspeed (Zentrum für Europäische Wirtschaftsforschung (ZEW), 1999)
Tax competition arguments suggest that governements that operate in an open economy (such as local governments) should not and will not rely on non-benefit taxes, such as the income tax. Yet we observe reliance on income taxes by local governments in many countries, and such reliance changes over ime. Evidence from a panel data set of 13 OECD countries over the period 1975-1984 suggest that competition between levels of government (resulting in a vertical fiscal externality) and between governments at the same level (resulting in a horizontal fiscal exterbality) provide some economic rationale for these changes. Moreover, the evidence indicates that the vertical and horizontal fiscal externalities interact. These results have some interesting implications for fiscal policy in the European Union, particularly as the EU continues to evolve. One implication for the EU is that enlargement that increases tax base disparities within the EU (and is not accompanied by an EU-level income tax) will tend to lower national income tax rates, although this must be qualified because it also depends on the mobility of the population. A second implication is that fiscal expansion of the EU to include an EU-level income tax may tend to lower the reliance of national government om income taxes though the vertical externality, but may also tend to equalize tax bases across countries, and so increase reliance on national income taxes though the horizontal externality.
Keywords: H1; H77; H87; 330; Tax competition; Tax structure; Fiscal federalism; International taxation; Steuerwettbewerb; Steuersystem; Finanzföderalismus; Schätzung; OECD-Staaten; Steuerpolitik; EU-Steuerrecht; EU-Staaten